Measurement Invariance of the Depression Anxiety Stress Scales-21 Across Gender in a Sample of Chinese University Students - Lu, Shan; Hu, Shuqing; Guan, Yuhuan; Xiao, Jing; Cai, Dan; Gao, Zhihua; Sang, Zhiqin; Wei, Jie; Zhang, Xiaochi; Margraf, Jürgen (Frontiers in Psychology, 2018)
The Depression Anxiety Stress Scales-21 (DASS-21) has three 7-item subscales (depression, anxiety, and stress). The current study aims assess the gender-based measurement invariance of the DASS-21 questionnaire in a Chinese university student sample from five different cities. The sample was composed of 13208 participants (62.3% female, mean age of 19.7 years, SD age = 1.8). Multi-group confirmatory factor analysis revealed full measurement invariance for the three subscales. The findings support the measurement invariance of DASS-21 scores across gender. Future research on the DASS should include additional validation across ethnicities, and testing of all versions of the scale.